Pro-Kontra Kewenangan Mahkamah Konstitusi dalam Menguji Undang-Undang yang Mengatur Eksistensinya - Lailam, Tanto (Jurnal Konstitusi, 2015)
The Proâ€™s â€“ Conâ€™s of the Constitutional Court in the review of law in a regulated of the authority, since, it was a conflicting of procedural principles between â€œius curia novitâ€ with â€œnemo judex idoneus in propria causaâ€. Morever, the background by implication of Constitutional Court decisions, sometimes Constitutional Court making a â€œrule breakingâ€,Â  for examples: nullify of some of law if had reduction ofÂ  the authority, addition of constitutional authority to review of law before the 1945 Constitution amendment, additional authority to review of Government Regulation in lieu of law, and used non-constitution as a standard in the formal review, and others. On the other hand, the Constitutional Court also sometimes to choose aÂ Â  legal logic doesnâ€™t precise and anti-accountability principle. The Conflicts of the procedural principles canÂ  beÂ  resolvedÂ  byÂ  understandingÂ  philosophyÂ  ofÂ  purposes of law (justice value, legal certainly, utility principle), so that, the Court will have been prioritizing to â€œius curia novitâ€ principle and it ignored â€œnemo judex idoneusÂ  in propria causaâ€principle, it is intended that the enforcement of the constitution (values) and the state of the Indonesian rule of law, as well as for the Court to aims decided of constitutional issues and to aim the protection of constitutional rights.